Effects of Ag Incorporation on the Band Structures and Conductivity Types of (Cu1‐xAgx)2ZnSnS4 Solid Solutions. Issue 9 (18th July 2018) - Liang, Xizhuang; Wang, Peng; Huang, Baibiao; Zhang, Qianqian; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying
Abstract: In this paper, (Cu1‐ x Ag x )2 ZnSnS4 (CAZTS) solid solutions were prepared through a facile hydrothermal and post‐calcination treatment method. The gradual shift of the X‐ray diffraction pattern (XRD) reveals that the CAZTS samples are solid solutions without impurities. UV‐Vis‐NIR diffuse reflectance spectroscopy (DRS) indicates the band gaps of the solid solutions can be tuned continuously by controlling the Ag/(Ag+Cu) molar ratios ( x ). The H2 evolution rate increases with the substitution amount of Ag. When the Ag doping amount exceeds 0.6 in CAZTS solid solutions, the conductivity of the semiconductor changes from p type to n type, as proven by photocurrent density‐applied potential curves and Motte‐Schottky plots. Our results prove that Ag incorporation plays a key role in the band structures and conductivity types of (Cu1– x Ag x )2 ZnSnS4 solid solutions. Abstract : Fine‐tuned : (Cu1‐ x Ag x )2 ZnSnS4 solid solutions are prepared through a facile hydrothermal and post‐calcination treatment method. The band gaps of the solid solutions can be tuned continuously by controlling the Ag/(Ag+Cu) molar ratios. When the Ag doping amount exceeds 0.6 in CAZTS solid solutions, the conductivity of the semiconductor changes from p type to n type proved by photocurrent density‐applied potential curves and Motte‐Schottky plots.